Experimental investigation on longitudinal shear of composite slab based on BS5950 1994 : part 4 - Tay, Poh Chien. (2012)
Composite slab has gaining widely use in Singapore construction as composite slab have faster, lighten and economical construction in building. The strength of composite slab is normally governed by the longitudinal shear bond failure which is the deboning activities that happened between the profiled steel sheet and concrete interface.